The Effect of Green Accounting and Enviromental Social Governance on Company Profitability with Firm Size as a Moderation Variable - M. Budiantara (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
The purpose of this study is to determine the influence of Green Accounting and Environmental, Social, Governancae (ESG) on Profitability. In addition, it is also to find out whether the company size variable can moderate the relationship between Green Accounting and company Profitability, as well as the relationship between ESC and company Profitability. The study used a sample of 44 companies engaged in the mining sector, which are listed on the Indonesia Stock Exchange in 2022 and 2023. The analysis tool used is Multiple Linear Regression. The results of the study show that Green Accounting and ESG are partially related to Profitability. Company size can moderate the relationship between Green Accounting and Profitability, but company size can